Combat-related guilt and the mechanisms of exposure therapy. (March 2018) - Trachik, Benjamin; Bowers, Clint; Neer, Sandra M.; Nguyen, Vu; Frueh, B. Christopher; Beidel, Deborah C.
Abstract: Exposure therapy (EXP) is one of the most widely used and empirically supported treatments for PTSD; however, some researchers have questioned its efficacy with specific populations and in targeting specific symptoms. One such symptom, guilt, has garnered increased attention in the PTSD treatment literature, as it is associated with worse symptomatology and outcomes. The current study examined cognitive changes in guilt in response to Intensive (3-week) and Standard (17-week) Trauma Management Therapy (TMT), and the potential mechanisms underlying TMT treatment. TMT is an exposure based intervention that does not include an emotional processing component after the imaginal exposure session. A portion of the sample completed measures of guilt. As a result, sample size for these analyses ranged from 39 to 102 and varied by the domain and measure. Of the 102 individuals that completed the PTSD Checklist- Military Version, 42 completed the Trauma Related Guilt Inventory, and 39 completed the Clinician Administered PTSD Scale supplemental guilt items. Participants reported significant reductions in trauma-related guilt symptoms over the course of the TMT interventions. Greater reductions in avoidance and prior session general arousal predicted the reduction of guilt symptoms. Exposure therapy may be effective in reducing trauma-related guilt even in the absence of the emotional processing component of treatment. Highlights: This study provides evidence that trauma-related guilt in Veterans may be reduced through mechanisms of exposure therapy. LMER analyses were used to investigate specific therapeutic mechanisms that may contribute to beneficial changes in guilt. Exposure therapy may be effective in reducing guilt symptoms in the absence of the emotional processing component of treatment.